A simple experimental set‐up to disentangle the effects of altered temperature and moisture regimes on soil organisms. Issue 10 (11th June 2015) - Krab, Eveline J.; Cornelissen, Johannes H.C.; Berg, Matty P.; Freckleton, Robert
Summary Climate manipulation experiments in the field and laboratory incubations are common methods to study the impact of climate change on soils and their biota. However, both types of methods have drawbacks either on their mechanistic interpretation or ecological relevance. We propose an experimental set‐up that combines the best of both methods and can be easily obtained by modifying widely available Tullgren soil fauna extractors. This set‐up creates or alters temperature and moisture gradients within intact field soil cores, after which soil biota, their activity and vertical movements can be studied. We assessed the performance and demonstrated the applicability of this set‐up through a case study on Collembola response to changes in microclimatic gradients in peat bogs. Warming created a vertical temperature gradient of 14°C in peat cores without varying soil moisture conditions, while at a given temperature regime, precipitation and drought treatments shifted natural soil moisture gradients to 'wetter' and 'drier', respectively. This allowed for disentangling interacting warming and moisture effects on soil fauna. In our case study, Collembola communities showed peat layer‐specific responses to these climate treatments. Warming decreased Collembola density and altered community composition in the shallowest layer, whereas precipitation increase affected Collembola community composition in the deepest layer. We showed that climate change can have layer‐specific effects on soil organisms that are 'hidden' by not taking microclimatic vertical gradients into account. This experimental set‐up facilitates studying (multitrophic) organism responses to climate changes, with only a small adjustment of equipment that is often already present in soil ecology laboratories. Moreover, this set‐up can be easily customized to study many more other research questions related to wide‐ranging organisms and ecosystems.